MULTICULTURAL CURRICULUM DEVELOPMENT MODEL ( CASE STUDY OF CURRICULUM PLANNING FOR SMA NEGERI 2 KEDIRI ): MULTICULTURAL CURRICULUM DEVELOPMENT MODEL ( CASE STUDY OF CURRICULUM PLANNING FOR SMA NEGERI 2 KEDIRI ) - Ramdhan, Tri Wahyudi (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2020)
ABSTRACT In the research, this time will try to discuss curriculum development based on multicultural education. Given the very diverse curriculum development, which consists of elements (1) planning ; (2) implementation ( 3 ) evaluation. But in this research, not all elements of curriculum development are a concern, but will only be focused on elements of curriculum planning done by SMA 2 Kediri. This approach uses a qualitative approach to the type of case study. Whereas in collecting data using participatory observation, in-depth interviews, and documentation. And the data collected was analyzed using an interactive analysis model. Results of the research showed that although the p Planning for curriculum at the high school one using parallel model through three stages., Namely (1) the planning strategic, (2) planning program, and (3) planning learning activities to produce products containing the dimensions of multicultural through a process that also includes multicultural dimension Keywords: Curriculum, Model, Multicultural